2022
DOI: 10.21744/lingcure.v6ns1.2186
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting accountability village fund management

Abstract: The purpose of this study is to investigate whether or not the accountability of village fund management is affected by factors such as prosocial behaviour, the competency of apparatus, internal control, and external pressure. All of the village fund managers that work for the 13 different village governments located in the Gunungkidul Regency of the Special Region of Yogyakarta make up the sample for this study. Purposive sampling was utilized as the method of choice for data collection in this investigation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Because the village administration is the only one responsible for reporting on the internal control system to the center, it has no effect on accountability and doesn't reach the goal of accountability, which is to win the public's trust. This research is backed up by research by Diansari et al (2022) which says that internal control has no significant effect on accountability. Abuse of public funds will still happen, even if there are controls, if the authorized official wants to abuse his power and make the public doubt that the financial statements are accurate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the village administration is the only one responsible for reporting on the internal control system to the center, it has no effect on accountability and doesn't reach the goal of accountability, which is to win the public's trust. This research is backed up by research by Diansari et al (2022) which says that internal control has no significant effect on accountability. Abuse of public funds will still happen, even if there are controls, if the authorized official wants to abuse his power and make the public doubt that the financial statements are accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to link prosocial behaviour (Diansari, 2022;Mahayani 2017), and the use of information technology (Syafaruddin et al, 2019); (Yudianto, 2017); (Wardhani, 2017) but research on village funds is still interesting With the size of village funding, the accountability mechanism is very complex, therefore fraud is feasible. Kapanewon Imogiri is one of the recipients of village funding in Bantul Regency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of managing village funds, the behavioral factors of the village government play an important role in the success of village financial management. Prosocial behavior is the behavior of helping others without expecting rewards as a sense of responsibility in socializing with the community (Diansari et al, 2022). A person in various cultures prefers to help others who belong to their group (in-group) compared to someone who is not from their group (outgroup) (Brewer & Brown, 1998).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In terms of existing research, people have been shown to consciously cope with emotional distress through certain purchasing behaviours. For example, Liang et al (2023) finds that depression positively and significantly influences impulsive and compulsive buying behaviour.…”
Section: The Relationship Between Anxiety and Panic Buyingmentioning
confidence: 99%